Study of peak capacities generated by a porous layered radially elongated pillar array column coupled to a nano-LC system. Issue 5 (23rd January 2019) - Futagami, Shunta; Hara, Takeshi; Ottevaere, Heidi; Terryn, Herman; Baron, Gino V.; Desmet, Gert; De Malsche, Wim
Abstract : The performance of a porous-layered radially elongated pillar (PLREP) array column in a commercial nano-LC system was examined by performing separation of alkylphenones and peptides. Abstract : The performance of a porous-layered radially elongated pillar (PLREP) array column in a commercial nano-LC system was examined by performing separation of alkylphenones and peptides. The mesoporous silica layer was prepared by sol–gel processing of a mixture of tetramethoxysilane and methyltrimethoxysilane on REPs filling a 16.5 cm long, 1 mm wide channel (three lanes of 5.5 cm long channels connected by turns). The minimum plate height of 1.4 μm for octanophenone ( k = 2.21) observed in isocratic mode is 5 times smaller than the smallest off-column plate height previously reported for porous pillar array columns for a retained component. This advantage is related to the earlier introduced shape of the radially elongated pillar bed that outperforms the cylindrically shaped pillar bed in terms of the plate height. In gradient mode, maximum conditional peak capacities of 220 (for a mixture of thiourea and 7 alkylphenones, t G = 180 min) and 160 (for a cytochrome c digest, t G = 150 min) were obtained. These results indicate excellent potential for implementation of this sol–gel layer in pillar array column formats.